The Effect of Production Value, Domestic Investment, Nin-Oil and Gas Export Value on Provincial GDP in Indonesia 2019 - Aji, Gunawan; Fauzan, Taqwa; Thusqdiah, Wanda Alif; Damayanti, Putri (Cattleya Darmaya Fortuna, 2023)
Some important factors that affect the economic growth of a province in Indonesia include production, domestic investment, and non-oil and gas exports. So that the increase in GDP shows the enthusiasm of the economy to move and expand so that it will affect economic growth in the area. This study uses quantitative research, researchers want to know how much the Influence of Production Value, Domestic Investment, and Non-Oil and Gas Exports on Provincial GDP in Indonesia in 2019. In testing this data using various test components and hypothesis tests in processing the data. Production has a positive and significant effect on Indonesia's GDP in 2019.Domestic Investment has a strong impact and positive relationship and provides an increase to Indonesia's GDP if domestic investment increases. Non-oil and gas exports have a significant influence on Indonesia's GDP